Estimating maternity ward birth attendant time use in India: a microcosting study. Issue 2 (7th February 2022) - Lofgren, Katherine T; Bobanski, Lauren; Tuller, Danielle E; Singh, Vinay P; Marx Delaney, Megan; Jurczak, Amanda; Ragavan, Meera; Kalita, Tapan; Karlage, Ami; Resch, Stephen Charles; Semrau, Katherine E A
Abstract : Objectives: Despite global concern over the quality of maternal care, little is known about the time requirements to complete the essential birth practices. Using three microcosting data collection methods within the BetterBirth trial, we aimed to assess time use and the specific time requirements to incorporate the WHO Safe Childbirth Checklist into clinical practice. Setting: We collected detailed survey data on birth attendant time use within the BetterBirth trial in Uttar Pradesh, India. The BetterBirth trial tested whether the peer-coaching-based implementation of the WHO Checklist was effective in improving the quality of facility-based childbirth care. Participants: We collected measurements of time to completion for 18 essential birth practices from July 2016 through October 2016 across 10 facilities in five districts (1559 total timed observations). An anonymous survey asked about the impact of the WHO Checklist on birth attendants at every intervention facility (15 facilities, 83 respondents) in the Lucknow hub. Additionally, data collectors visited facilities to conduct a census of patients and birth attendants across 20 facilities in seven districts between June 2016 and November 2016 (six hundred and ten 2-hour facility observations). Primary and secondary outcome measures: The primary outcome measure of this study is the per cent of staff time required to complete the essential birth practices included in the WHO Checklist. Results: When birth attendants were timed, we found practices were completed rapidly (18 s to 2 min). As the patient load increased, time dedicated to clinical care increased but remained low relative to administrative and downtime. On average, WHO Checklist clinical care accounted for less than 7% of birth attendant time use per hour. Conclusions: We did not find that a coaching-based implementation of the WHO Checklist was a burden on birth attendant's time use. However, questions remain regarding the performance quality of practices and how to accurately capture and interpret idle and break time. Trial registration number: NCT02148952 .